2004
DOI: 10.1002/malq.200310121
|View full text |Cite
|
Sign up to set email alerts
|

On Schnorr and computable randomness, martingales, and machines

Abstract: We examine the randomness and triviality of reals using notions arising from martingales and prefix-free machines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 20 publications
1
58
0
Order By: Relevance
“…While all reasonable relativizations of Martin-Löf randomness coincide, this is not the case for other notions of randomness. For example, Miyabe [32], following work of Downey, Griffiths and LaForte [13], examined a partial relativization of Schnorr randomness with only truth- A -test, and so every set which is Demuth random relative to A is also Demuth BLR A -random. If A is computably dominated, then bounding by A-computable functions and bounding by computable functions are the same, and so the notions coincide.…”
Section: Introductionmentioning
confidence: 99%
“…While all reasonable relativizations of Martin-Löf randomness coincide, this is not the case for other notions of randomness. For example, Miyabe [32], following work of Downey, Griffiths and LaForte [13], examined a partial relativization of Schnorr randomness with only truth- A -test, and so every set which is Demuth random relative to A is also Demuth BLR A -random. If A is computably dominated, then bounding by A-computable functions and bounding by computable functions are the same, and so the notions coincide.…”
Section: Introductionmentioning
confidence: 99%
“…real. This contrasted with the theorem of Downey, Griffiths and LaForte [20] who showed that if a left-c.e. real was Kurtz random, then its Turing degree must resemble the halting problem in that it must be high (i.e.…”
Section: Theorem 334 (Wang [103]) a Real α Is Kurtz Random Iff Thermentioning
confidence: 76%
“…Schnorr trivial reals behave quite differently than do Schnorr low reals and the Ktrivials. Downey and Griffiths constructed a Schnorr trivial real and Downey, Griffiths and LaForte [20] showed that they can even be Turing complete, though they do not occur in every computably enumerable Turing degree. Subsequently, they have been investigated by Johanna Franklin [31].…”
Section: Theorem 59 (Nies [76]) Suppose That a Is Low For Computablmentioning
confidence: 99%
“…set A is autocomplex if and only if it is Turing equivalent to the halting problem (see Downey and Hirschfeldt [13, Theorem 8.16.7]). Downey, Griffiths and LaForte [12, Theorem 8] showed that there exists a c.e. Schnorr trivial set which is Turing equivalent to the halting problem.…”
Section: Proposition 5 Low (Sr Sr) ⊆ Low(mlr Wr)mentioning
confidence: 99%